The summer of Sunshine and Margot - Mallery, Susan (Don Mills, Ontario : HQN, 2019)
The Baxter sisters come from a long line of women with disastrous luck in love. But this summer, Sunshine and Margot will turn disasters into destiny.
Includes questions for discussion.
Keywords: Single fathers -- Fiction; Celebrities -- Fiction; Twins -- Fiction; Romance fiction